2006
DOI: 10.1192/bjp.bp.105.019489
|View full text |Cite
|
Sign up to set email alerts
|

Adherence therapy for people with schizophrenia

Abstract: This effectiveness trial provides evidence for the lack of effect of adherence therapy in people with schizophrenia with recent clinical instability, treated in ordinary clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 24 publications
2
118
1
1
Order By: Relevance
“…The sample size calculation was based on the average effects size on symptom severity (Positive and Negative Syndrome Scale; 0.48 to 0.54) and level of medication adherence (Positive and Negative Syndrome Scale; 0.46 to 0.52) at immediately post-intervention in four clinical trials of AT [8,16] or psycho-education programs with medication management as core components in schizophrenia [1,19]. With the level of statistical significance set at P  = 0.05 (two-sided) and a study power of 80 %, the sample size was 47 per group to detect an average effect size (Cohen’s d) of 0.50 on the above two outcomes, using G*Power 3.1 for Windows [20], taking into account an attrition rate of 20 % [10,19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size calculation was based on the average effects size on symptom severity (Positive and Negative Syndrome Scale; 0.48 to 0.54) and level of medication adherence (Positive and Negative Syndrome Scale; 0.46 to 0.52) at immediately post-intervention in four clinical trials of AT [8,16] or psycho-education programs with medication management as core components in schizophrenia [1,19]. With the level of statistical significance set at P  = 0.05 (two-sided) and a study power of 80 %, the sample size was 47 per group to detect an average effect size (Cohen’s d) of 0.50 on the above two outcomes, using G*Power 3.1 for Windows [20], taking into account an attrition rate of 20 % [10,19].…”
Section: Methodsmentioning
confidence: 99%
“…These nurse therapists had received two full-days training by the research team based on both the AT instructor program developed by Gray et al [11] and a psycho-education program for Chinese patients with schizophrenia [1,21]. The trained nurses were provided with supervised practices on AT for at least three outpatients with schizophrenia until the supervisors (the first and second authors) agreed and confirmed the consistency and competency of their implementation of the treatment protocol (over 90 % of items rated as ‘Fully competent’), using a validated competency scale of AT [16]. During the therapy, three sessions were randomly selected for each nurse therapist, audio-taped (with the nurses’ and participants’ prior consents) and assessed by two raters (researchers) to monitor the treatment fidelity using the same competency scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a well-conducted, adequately powered RCT found adherence therapy to be ineffective in improving adherence, psychotic symptoms or quality of life in people with schizophrenia (Gray et al, 2006).…”
Section: Interventions To Improve Adherencementioning
confidence: 99%
“…Many other randomized controlled trials of patient education for people with schizophrenia have also reported no QoL differences between different education methods [46][47][48]. Nevertheless, both computer-based education and education with standard leaflets can offer more systematic alternatives to standard patient education.…”
Section: Discussionmentioning
confidence: 97%